Burnout syndrome in secondary school teachers: The influence of psychological capital and school type - Hernández, Montserrat Monserrat; Pérez, Joaquín Tarifa; Shchotkina, Valeriia; García, Darío Salguero (Edelweiss Applied Science and Technology, 2025)
This study explores the joint influence of school type (public or state-subsidized private) and levels of psychological capital on teacher burnout. A cross-sectional study was conducted with a sample of 1,046 secondary school teachers (46.7% from public schools), using the Shirom–Melamed Burnout Measure and the reduced Ipsicap scale. Independent samples t-tests were performed to compare scores between teachers from different school types across each dimension of burnout and psychological capital. Additionally, a two-way ANOVA was conducted to assess the combined effect of school type and psychological capital levels on burnout. The results indicate that teachers in public schools exhibit higher burnout, particularly physical fatigue, compared with those in state-subsidized private schools. Both school type and psychological capital influenced burnout, with psychological capital acting as a protective factor. A significant interaction between the two variables was also observed. It is concluded that fostering psychological capital may serve as an effective strategy to prevent burnout, especially in contexts with higher demands or fewer resources. These findings suggest that enhancing psychological capital among teachers could be an effective approach for burnout prevention, particularly in educational settings with increased demands or limited resources.